Your Midlife Crisis or mine? The journey of how children experience their parents’ “Midlife Crisis” - Sun, Zhengfei (Nanyang Technological University, 2020)
Midlife Crisis is a term used in many occasions, such as an excuse for a middle-aged’s unusual behavior, a theme for a comedy, an eye-catching title for an article, or a topic we would laugh about. It is a term where most people make fun of but yet too sensitive to share personal experiences. However, in reality, Midlife Crisis can be devastating to a family as it gives rise to a lot of misunderstanding and miscommunication between members of a family. In some cases, it may even lead to mental illnesses. Many of the behavior changes could affect their family members emotionally without the awareness of the middle-aged. This project investigates how age-related changes have affected the children of the middle-aged, and to visually present the effects of Midlife Crisis through the perspective of their children. The results of the study may serve as a visual guide to help people to learn more about the impacts of Midlife Crisis and also to appreciate any behavior changes during this period.